PENGARUH KUALITAS DESAIN WEBSITE TERHADAP NIAT PEMBELIAN DIMEDIASI OLEH PERSEPSI KUALITAS PRODUK PADA LAZADA.CO.ID - Ulyatul Nazirah, Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
The purpose of this study is to determine the influence of website design quality towards purchase intention, with perception of the product quality as a mediating variable. The samples used in this study were 170 respondents who have accessed and made purchases on Lazada.co.id website. The sampling technique used was Purposive Sampling. Hierarchical Linear Modeling (HLM) method was used as a method of analysis to determine the effect of the variables involved. The results of this study showed that the website design quality had a significant effect toward purchase intention. In addition, the results showed that the perception of the product quality variable partially mediated the influence of the website design quality toward purchase intention. The better the owned website design quality, the better the perception of the product quality, thus the higher the customer’s purchase intention would be.